Orquestração de um pipeline de ferramentas para apoio ao ensino - Almeida, Rúben Lourenço Teixeira de (2022)
The variety and nature of tools that are nowadays used on both academic and professional contexts have been increasing over the past few years. With the non stopping evolving cycle that technology suffers on a daily basis, this is a consequence that will be even more noticeable in a not so distant future. As a result, several problems have emerged. How to handle all of the crucial tools in a simple and reliable way? How to structure that process so it can scale, in order to apply it whenever the tools are being used by several people? Services specialization, such as microservices, taking advantage of the core tools features, allows the automation of almost all the needed configurations required. This thesis focus on the design and implementation of a solution that enhances the ease and efficiency of creating and configuring working environments either of students or workers, being, however, more focused on the academic environment. To achieve this, a prototype tool has been developed, which consists in several services that when combined together are capable of creating and configuring a software development integration pipeline. The prototype is responsive to a certain configuration input and handles all the tasks needed in between the configuration steps, keeping the resulting pipeline always up to date.